2013
DOI: 10.1002/jsfa.6328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioactive‐rich extracts of pomegranate, persimmon, nettle, dill, kale andSideritisand isolated bioactives on arachidonic acid induced markers of platelet activation and aggregation

Abstract: These data show that bioactive-rich extracts of kale and pomegranate that are consumed as traditional plant foods of Black Sea area countries were effective in modulating platelet function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…This data also supports a role for active biopeptides in modulating in vivo platelet function. The ability to inhibit platelet function has previously been confirmed ex vivo in the presence of other vegetable bioactives [27]. Nonetheless, it is unclear why this occurs or what role this response might play in pathological conditions, other than in healthy individuals with normal-high non-treated hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…This data also supports a role for active biopeptides in modulating in vivo platelet function. The ability to inhibit platelet function has previously been confirmed ex vivo in the presence of other vegetable bioactives [27]. Nonetheless, it is unclear why this occurs or what role this response might play in pathological conditions, other than in healthy individuals with normal-high non-treated hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…The reduction in platelet P-selectin expression, following QGPJ supplementation, signifies the ability of QGPJ to reduce platelet degranulation and inhibit platelet α-granule release consequently assisting in reducing thrombotic risk. Similarly, in subjects with metabolic syndrome, polyphenol-rich extracts of kale and pomegranate have reduced P-selectin and GPIIb-IIIa expression in vitro (Konic-Ristic et al, 2013). QGPJ or PJ did not alter PAC-1 expression and consequently had no effect on the initial phase of activation involving the GPIIb-IIIa receptor.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, GPVI is involved in the protective effects observed with SFN treatment. It is interesting to note that SFN has already been previously shown to significantly inhibit platelet-neutrophil aggregation (along with P-selectin and GPIIb-IIIa expression) in subjects with metabolic syndrome versus healthy controls (Konić-Ristić et al, 2013). With respect to our study, whilst the effects of SFN on the interactions between leukocytes and platelets are not the main aim of our study, we found that SFN reduces expression of GPIIbIIIa and Pselectin on platelets which may reduce platelet-leukocyte interactions through P-selectin inhibition by increasing levels of cAMP followed by inhibiting intracellular signals (such as the PI3K/Akt and PLCγ2-PKC-p47 cascades) and ultimately inhibiting platelet activation.…”
Section: Figurementioning
confidence: 98%